2008
DOI: 10.1128/aac.01449-07
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Content, an Inaccurate Biomarker of Mitochondrial Alteration in Human Immunodeficiency Virus-Related Lipodystrophy

Abstract: Lipoatrophy is a prevalent side effect of antiretroviral treatment of human immunodeficiency virus (HIV)infection. Its mechanisms are still disputed but include mitochondrial toxicity and, in particular, mitochondrial DNA (mtDNA) depletion induced by nucleoside reverse transcriptase inhibitors. To obtain an integrated evaluation of the mitochondrial alteration in lipoatrophy, we investigated the DNA, RNA, and protein levels in 15 samples of abdominal subcutaneous adipose tissue from HIV-infected patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
4
22
0
2
Order By: Relevance
“…Remarkably, antiretroviral treatment of HIV patients which causes severe lipoatrophies, altered the expression of genes involved in FA oxidation, TCA cycle and oxidative phosphorylation in adipose tissue (47)(48)(49). These changes were associated to up-regulation of genes involved in oxidative stress (49,50). In particular, HIV antiretroviral protease inhibitors (PIs), which inhibit Zmpste24 activity and lead to prelamin A accumulation (51), induce the expression of oxidative stress markers in adipose tissue in a manner comparable to that observed in patients with LMNA mutations (52).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, antiretroviral treatment of HIV patients which causes severe lipoatrophies, altered the expression of genes involved in FA oxidation, TCA cycle and oxidative phosphorylation in adipose tissue (47)(48)(49). These changes were associated to up-regulation of genes involved in oxidative stress (49,50). In particular, HIV antiretroviral protease inhibitors (PIs), which inhibit Zmpste24 activity and lead to prelamin A accumulation (51), induce the expression of oxidative stress markers in adipose tissue in a manner comparable to that observed in patients with LMNA mutations (52).…”
Section: Discussionmentioning
confidence: 99%
“…73 More recently, Garrabou et al found significant mtDNA depletion and reduced mitochondrial oxidative function in adipocytes of HIVinfected ART-naïve individuals compared to uninfected controls. 74 The value of tissue mtDNA measurement has been questioned by Kim et al, 75 who confirmed findings of depleted mtDNA in adipose tissue of lipoatrophic HAART-treated patients, but found no decrease in mtDNA-dependent mitochondrial function and an actual compensatory increase in nuclear-driven mitochondrial biogenesis, suggesting that mtDNA depletion was not a good marker for mitochondrial function. In another cross-sectional study by Magaard et al, 34 mitochondrial DNA was lower in muscle biopsies from 24 patients with HIV on HAART than 10 ART-naïve HIV patients, but both groups demonstrated decreased PBL mtDNA compared to 11 healthy controls.…”
Section: Research History Of Nucleoside Reverse Transcriptase Inhibitmentioning
confidence: 78%
“…No accompanying changes were observed in the expression of the key regulator of mitochondrial biogenesis PPARG coactivator 1α ( PPARGC1A ) or in the mitochondrially associated uncoupling protein 2 ( UCP2 ) (Figure 1d), genes dysregulated in tNRTI-mediated SAT toxicity. 31,32 …”
Section: Resultsmentioning
confidence: 99%